Unusual oral presentation of acyclovir-resistant herpes simplex in an allogeneic haematopoietic stem cell transplant recipient. Issue 12 (30th December 2021) - Saunsbury, Thomas; Harte, Molly; Ion, Daniela
Abstract : The early engraftment phase of allogeneic haematopoietic stem cell transplantation can be associated with a number of oromucosal infective complications. While the routine use of prophylactic acyclovir has reduced the incidence of herpes simplex virus (HSV) reactivation, there is an increasing prevalence of acyclovir resistance within this cohort of patients. The authors present a case of acyclovir-resistant HSV reactivation in a 26-year-old woman 7 days post T-deplete sibling allograft on a background of combined cyclophosphamide and total body irradiation myeloablative conditioning, successfully treated with foscarnet and cidofovir therapy and discuss the differential diagnoses for early/late engraftment oral disease.